Clinical practice guidelines for the diagnosis and treatment of adult diffuse glioma‐related epilepsy. (26th June 2019) - Liang, Shuli; Fan, Xing; Zhao, Ming; Shan, Xia; Li, Wenling; Ding, Ping; You, Gan; Hong, Zhen; Yang, Xuejun; Luan, Guoming; Ma, Wenbin; Yang, Hui; et al.
Abstract: Background: Glioma‐related epilepsy (GRE) is defined as symptomatic epileptic seizures secondary to gliomas, it brings both heavy financial and psychosocial burdens to patients with diffuse glioma and significantly decreases their quality of life. To date, there have been no clinical guidelines that provide recommendations for the optimal diagnostic and therapeutic procedures for GRE patients. Methods: In March 2017, the Joint Task Force for GRE of China Association Against Epilepsy and Society for Neuro‐Oncology of China launched the guideline committee for the diagnosis and treatment of GRE. The guideline committee conducted a comprehensive review of relevant domestic and international literatures that were evaluated and graded based on the Oxford Centre for Evidence‐Based Medicine Levels of Evidence, and then held three consensus meetings to discuss relevant recommendations. The recommendations were eventually given according to those relevant literatures, together with the experiences in the diagnosis and treatment of over 3000 GRE cases from 24 tertiary level hospitals that specialize in clinical research of epilepsy, glioma, and GRE in China. Results: The manuscript presented the current standard recommendations for the diagnostic and therapeutic procedures of GRE. Conclusions: The current work will provide a framework and assurance for the diagnosis and treatment strategy of GRE to reduce complications and costs caused by unnecessary treatment. Additionally, it can serve as a reference for all professionals involved in the management of patients with GRE. Abstract : This is the first clinical practice guideline for glioma‐related epilepsy (GRE).·It was completed under the cooperation of epileptologists and neurosurgeons.·It provides recommendations for diagnostic and therapeutic procedures of GRE.